Need for Ethnic and Population Diversity in Psychosis Research - Burkhard, Carla; Cicek, Saba; Barzilay, Ran; Radhakrishnan, Rajiv; Guloksuz, Sinan (Schizophrenia bulletin, 2021)
Abstract This article aims to evaluate “racial”, ethnic, and population diversity—or lack thereof—in psychosis research, with a particular focus on socio-environmental studies. Samples of psychosis research remain heavily biased toward Western, Educated, Industrialized, Rich, and Democratic (WEIRD) societies. Furthermore, we often fail to acknowledge the lack of diversity, thereby implying that our findings can be generalized to all populations regardless of their social, ethnic, and cultural background. This has major consequences. Clinical trials generate findings that are not generalizable across ethnicity. The genomic-based prediction models are far from being applicable to the “Majority World.” Socio-environmental theories of psychosis are solely based on findings of the empirical studies conducted in WEIRD populations. If and how these socio-environmental factors affect individuals in entirely different geographic locations, gene pools, social structures and norms, cultures, and potentially protective counter-factors remain unclear. How socio-environmental factors are assessed and studied is another major shortcoming. By embracing the complexity of environment, the exposome paradigm may facilitate the evaluation of interdependent exposures, which could explain how variations in socio-environmental factors across different social and geographical settings could contribute to divergent paths to psychosis. Testing these divergent paths to psychosis will however require increasing the diversity of study populations that could be achieved by establishing true partnerships between WEIRD societies and the Majority World with the support of funding agencies aspired to foster replicable research across diverse populations. The time has come to make diversity in psychosis research more than a buzzword.